Wage Setting and Unemployment: Evidence from Online Job Vacancy Data - Oleksandr Faryna; Tho Pham; Oleksandr Talavera; Andriy Tsapin (Global Labor Organization (GLO), 2020)
This paper examines the relationship between labour market conditions and wage dynamics by exploiting a unique dataset of 0.8 million online job vacancies. We find a weak trade-off between aggregated national-level wage inflation and unemployment. This link becomes more evident when wage inflation is disaggregated at sectoral and occupational levels. Using exogenous variations in local market unemployment as the main identification strategy, a negative correlation between vacancy-level wage and unemployment is also established. The correlation magnitude, however, is different across regions and skill segments. Our findings suggest the importance of micro data's unique dimensions in examining wage setting – unemployment relationship.
Keywords: C55; E24; E31; E32; 330; Phillips curve; wage curve; heterogeneity; micro data; online vacancies